Personal health and physical fitness - Folawiyo, A.F.A. (Lagos : Joja Educational Research and Publishers Ltd., 1989)
This book is a needed volume in the growing physical fitness literature. It is not a traditional curriculum book or a methods and material text. Rather it is a combination of these and other aspects of basic physical fitness
Includes bibliographical references.
osc 30/01/2019
Loans
Keywords: Physical Fitness - Health aspect